STUDY OF TUMOR MICROENVIRONMENT AND HOST RESPONSE IN COLORECTAL CANCER: IMMUNOHISTOCHEMICAL AND CLINICOPATHOLOGICAL APPROACH - NORIA OTHMAN RAFFALLA; SUZAN MOHAMED FAROUK HELAL; AMANY ABD EL-BARY ABD EL-LATIF; RASHA OMAR ELSAKA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study aimed to evaluate the immunohistochemical expression of forkhead boxP3 (Foxp3), CD8, CD68, and CD21 in stroma between tumor cells of colorectal cancer (CRC) patients and examines the relationship between these variables and clinicopathological parameter and patients’ prognosis. Methods: In this work, 50 cases of colorectal carcinomas were included and immunohistochemical evaluation of Foxp3, CD8, CD68, and CD21 in tumor tissue samples. Results: Tumor-infiltrating lymphocytes (TILs) including cytotoxic T cells and regulatory T cells as well as tumor-associated macrophages and follicular dendritic cells (FDCs) were studied in the stroma of the tumor using immunostaining technique for CD8, Foxp3, CD68, and CD21, respectively. Cases were followed up. CD8-positive cytotoxic T cells, Foxp3-positive regulatory T cells, and CD21 positive-FDCs were significantly more pronounced in early tumors and those with longer overall survival. On the other hand, CD68 positive macrophages were more encountered in late stage and metastatic tumors as well as tumors with shorter overall survival, but these results not reached the level of significance. Conclusion: We concluded that (TILs) and FDCs are conferring better prognosis in CRCs, they may act synergistically in stimulating a protective immune response in the tumor microenvironment that hinders tumor progression, while the role of tumor-associated macrophages in CRCs is still controversial and needs further studies.